If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -1) + -3x = 8 Reorder the terms: 2(-1 + x) + -3x = 8 (-1 * 2 + x * 2) + -3x = 8 (-2 + 2x) + -3x = 8 Combine like terms: 2x + -3x = -1x -2 + -1x = 8 Solving -2 + -1x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 8 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 8 + 2 -1x = 8 + 2 Combine like terms: 8 + 2 = 10 -1x = 10 Divide each side by '-1'. x = -10 Simplifying x = -10
| 8-2x=2x-5x | | 1x+3(4)=48 | | 9(-10)+160= | | -6h+2=-46 | | x+7=-3+3x | | .60x+.30(90)=.50(x+90) | | 6=18b | | 3x+15=12b-3b | | x*-5=10 | | 16t^2-128+400=0 | | 2a+24-3a=5a | | 8p-4=7p-2 | | n^2-34n-251=0 | | t^2-8+25=0 | | 1-m=1-m | | 16.28+8=100 | | -4n+2=-13-7n | | x^7-5x+6=0 | | 13x+23y=-5 | | -6+4p=5p-4 | | -3+2x-9=9 | | -10(3+2)-7= | | 569.7844=3135.6289h | | v+4=3v-6 | | 2=-2x+25 | | -7x=-16 | | 12+x-2x=-4+x | | 5s-11=13+s | | f(x+7)=x^2+8x+5 | | -7-7x=-16 | | 12x+6=x | | 5v-2=2+2v-2+1 |